Health Information Literacy: Accompaniment Counseling the Proper Use and Storage of Medicines for Flood Victims Communities in South Kalimantan - jamiatul hamidah (Borneo Community Development, 2021)
When floods hit South Kalimantan in mid-January 2021, many residents lived in evacuations such as schools, mosques, or sports buildings. Flood conditions can cause various diseases such as skin diseases, fever, diarrhea, flu, coughs, and so on. Therefore, refugee camps were chosen as the main targets to educate the public on the proper and correct use and storage of drugs. With this educational activity, it is hoped that it can increase public knowledge in the correct use and storage of medicines. In addition, this activity is also aimed at public readability of the various information printed on medicine packages. The method used in counseling the correct use of drugs and drug storage is carried out in several stages. The first stage is to conduct a survey and analysis of community needs for medicines while in the evacuation site. The second stage is to prepare medicines in coordination with several parties such as medical personnel and volunteers. The third stage, directly visiting the refugee camps, including in Pengambangan Village, East Banjarmasin District. The fourth stage, people who have health complaints, are given medical treatment, then educated about how to use the correct medicine. Finally, certain medicines are handed over to displaced residents as backup medicines to be stored. If at any time they need it, it is hoped that they will understand how to use it. The conclusion is that public knowledge of the proper use and storage of drugs is still low. With the counseling carried out to the flood victims in the evacuation camps, it has increased knowledge about the use of appropriate medicines. In addition, this counseling also increases public health information literacy.